Parietal and temporal activity during a multimodal dance video game: An fNIRS study - Tachibana, Atsumichi; Noah, J. Adam; Bronner, Shaw; Ono, Yumie; Onozuka, Minoru (Neuroscience letters, 2011)
► fNIRS permits insight into timing of cortical hemodynamics during motor tasks. ► Oxy-Hb changes were assessed in parietal and temporal areas during game-play. ► fNIRS detected increased oxy-hemoglobin changes in relation to task complexity. ► Oxy-Hb increase peaked early in the task in the superior parietal lobe. ► Oxy-Hb increase peaked midway in the task in the superior temporal gyrus. Using functional near infrared spectroscopy (fNIRS) we studied how playing a dance video game employs coordinated activation of sensory-motor integration centers of the superior parietal lobe (SPL) and superior temporal gyrus (STG). Subjects played a dance video game, in a block design with 30 s of activity alternating with 30 s of rest, while changes in oxy-hemoglobin (oxy-Hb) levels were continuously measured. The game was modified to compare difficult (4-arrow), simple (2-arrow), and stepping conditions. Oxy-Hb levels were greatest with increased task difficulty. The quick-onset, trapezoidal time-course increase in SPL oxy-Hb levels reflected the on-off neuronal response of spatial orienting and rhythmic motor timing that were required during the activity. Slow-onset, bell-shaped increases in oxy-Hb levels observed in STG suggested the gradually increasing load of directing multisensory information to downstream processing centers associated with motor behavior and control. Differences in temporal relationships of SPL and STG oxy-Hb concentration levels may reflect the functional roles of these brain structures during the task period. NIRS permits insights into temporal relationships of cortical hemodynamics during real motor tasks.